APLIKASI BERBAGAIJENIS PUPUK ORGANIK CAIR TERHADAP PERTUMBUHANDAN PRODUKSI EMPAT VARIETAS TANAMAN KACANGHIJAU(Vigna radiata. L) - Parlinggoman Sinaga; Maizar Maizar; Fathurrahman Fathurrahman (DINAMIKA PERTANIAN, 2017)
The purpose of this study was to determine the interaction and main effects of various types of liquid organic fertilizer on the growth and production of four varieties of green bean plants. This study uses a factorial Randomized Complete Design. The first factor is a variety of liquid organic fertilizer (C) consisting of 4 levels, while the second factor is a variety of green bean varieties (V) consisting of 4 levels. Of these two factors, there are 16 combinations of treatments with 3 replications. Then there are 48 experimental units. Each unit consists of 15 plants. The parameters observed were as follows: plant height and flowering age. Data from observations from each treatment were analyzed statistically and continued with a further test of Honest Real Difference (BNJ) at the level of 5%. The results showed that both the interaction and the main influence of giving liquid fertilizer to various varieties influenced plant height and flowering age. Interactively, the best treatment was in the administration of POMI 4 cc / l in varieties of the Murai variety (C2V4). Singularly the best treatment for POMI 4 cc / l (C2) in the best variety is Walnuts (V1).